ChemInform Abstract: CN‐Mayenite Ca12Al14O32(CN)2: Replacing Mobile Oxygen Ions by Cyanide Ions. Issue 5 (February 2015) - Lerch, Martin; et al., et al.
Abstract The title compound is prepared by a solid‐gas reaction using a 12:6:2 molar mixture of freshly calcined CaO, α‐Al2O3, and AlN heated under N2 (1423 K, 4 h, N2 pressure of 105 Pa).